'I never felt like I was alone': a holistic approach to supporting students in an online, pre-university programme. (2nd September 2019) - McDougall, Jenny
ABSTRACT: Programmes that provide adult learners with an alternative pathway to university typically offer considerable support. Students in such enabling, or access, programmes are increasingly choosing to study online because of the flexibility it affords, yet little is known about how well this mode of learning caters for their needs. The aim of this study, therefore, is to establish how well supported enabling students in an online programme feel, and what particular aspects of support work best for these students. The concept of 'holistic' learning, defined in humanistic terms, provides a framework for this discussion. Drawing on data from subject evaluations and an online survey, this qualitative case study compares the experiences of online and on-campus students in an introductory, study skills subject. Significantly, both cohorts reported similar levels of satisfaction with the support received. Regular communications and encouragement from their lecturers were very important to online students, while contact with fellow students was generally not a priority. Online resources, such as lecture recordings and short 'talking head' videos, helped students learn but also personalised their experience. Findings suggest that a supportive online environment can be achieved, thus going some way to addressing students' personal as well as academic needs, and challenging negative stereotypes around the anonymity of online learning.